Analisis Hukum atas Putusan Hakim Terhadap Wanprestasi dalam Perjanjian Utang Piutang (Studi Putusan Nomor 1095/Pdt.G/2024/PN Mdn) - Ayu Mentari Sinambela; Iin Hot Prinauli Purba (CV WAHANA PUBLIKASI, 2026)
This study aims to investigate a breach of contract in a case illustrated by the studied decision. The Medan District Court Decision Number 1095/Pdt.G/2024/PN Mdn serves as a compelling case for legal analysis in civil law. The panel of judges deliberated on the legal facts in their ruling. The judge’s legal considerations are crucial as they demonstrate the application of civil law to the specific facts in contention. This study seeks to identify and analyze the facts of the case and the legal facts underpinning the examination of the Medan District Court Decision Number 1095/Pdt.G/2024/PN Mdn, as well as to evaluate the judge’s legal reasoning in rendering a verdict on the civil matter. This study employs a normative legal research method. The findings suggest that the Defendant’s actions, which resulted in losses for the Plaintiffs, may be legally classified as a breach of contract or breach of promise, as they evidently contravene the stipulations of Article 1243 of the Civil Code. This provision mandates that the duty to indemnify for expenses, damages, and interest arises if the debtor, although being deemed negligent, fails to fulfill his duties or fulfills them after the designated timeframe has elapsed. The judge determined that the Defendant’s actions constituted a violation of the agreement, resulting in a breach of contract or breach of promise. This decision exemplifies the appropriate application of civil law regarding evidence, the enforcement of legal norms, and the evaluation of the facts presented in court.